Effectiveness of QRIS Implementation in Supporting Digital Transactions for MSMEs - Bachtiar, Fadli; Firmansyah, Ismail Alfi; Fikri, Angger Rizalul (Journal of Multimedia Trend and Technology, 2025)
This study evaluates the effectiveness of QRIS implementation for MSMEs by examining its impact on transaction efficiency, business growth, financial transparency, customer adoption, and challenges encountered. Data were gathered using structured questionnaires and analyzed using descriptive statistics as part of a quantitative descriptive approach. The results show that QRIS positively impacts MSME performance. More than 90% of respondents believed that QRIS enables digital payments, and 61.3% of respondents embraced QRIS primarily for transaction simplicity. In terms of company success, 80.7% of respondents said that the number of transactions increased, with 35.5% reporting notable increases and 45.2% reporting just modest gains. With 96.8% of respondents saying that QRIS helps or substantially helps with transaction recording, it also promotes financial transparency. Given that 48.4% of their consumers noted that only 40–70% of them utilize QRIS, the frequency of consumer use remains moderate. Notwithstanding the advantages, a number of obstacles still exist, such as erratic internet connections (35.5%), a lack of consumer adaptation (22.6%), technical malfunctions (16.1%), and worries about Merchant Discount Rate (MDR) costs, which over half of MSMEs said were onerous. In conclusion, QRIS has proven effective in supporting MSMEs' digital transformation, yet improvements in infrastructure, customer education, and fee structures are required to maximize its impact.